Geophysical and Hydrogeological Study for Evaluating Seawater Intrusion in Coastal Aquifers of Amphoe Cha-am, Changwat Phetchaburi - Sae-Ju, Jiraporn; Chotpantarat, Srilert; Thitimakorn, Thanop (Bulletin of Earth Sciences of Thailand, 2021)
The study area is a famous tourist coastal area, located in Amphoe Cha-am, Changwat Phetchaburi, where contains densely populated area. The need of a large amount of fresh water thus tends to be increased as well as intensive extraction of groundwater from coastal aquifers has decreased freshwater outflow to the sea and leads to local groundwater depression. Seawater intrusion is one of the rising problems in this area due to seawater movement inland and rising toward fresh water well. In this study, an integrated geophysical and hydrogeological study was carried out to evaluate seawater intrusion in coastal aquifers. The 22 dataset of vertical electrical sounding method (VES), is useful to identify variations in electrical characteristics of coastal aquifers. Hydrogeological characteristics were generated from drilling data, electric log data, measured static water levels, and well screen depths. By integrating both investigations, we found that seawater intrusion mainly occurs in Qcl aquifer at a depth of 30-50 meters and laterally intrudes about 7 kilometers inland. Furthermore resistivity values ranging between 0-10 Ωm, represents Qcl getting highly influenced by seawater intrusion, while resistivity values are in the range of 10-15 Ωm in Gr aquifer, suggesting that is partially influenced by seawater intrusion.